THE SUCCESS OF COMPANIES OPERATING IN THE AREA OF TAX HAVENS - ENEA CONSTANTIN; ENEA CONSTANTA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
What is an offshore company? It is a company operating outside the country in which it was established. What is a tax haven? It is a country or jurisdiction where companies have tax advantages usually zero tax. (eg Andorra, British Virgin Islands, Panama, Liechtenstein, Cayman Islands, Seychelles, Cyprus, Malta, etc. How do I open an offshore bank account? Opening an account is a particular problem, which is mostly open once the offshore company is established. Paradise is characterized by the absence levies tax as tax on the income of individuals or legal entities, in respect of succession duties, and of course as tax on capital. Consequently, these areas generally did not sign tax agreement designed to avoid double taxation, having nothing to negotiate in this direction; the several agreements signed disclaim reception facilities made available to foreign investors. Foreign source income will generally support the tax levy the maximum light source of local law provisions. The rule that a very low tax burden, or even an absence of tax levy, generates tax havens should be relaxed. In this paper we decided to present three main areas of interest are the old tax havens: banking and insurance companies, shipping companies and investment and development activities.